Site-selective fatty acid chain conjugation of the N-terminus of the recombinant human granulocyte colony-stimulating factor - Wang, Xu-Dong; Su, Zhi-Hao; Du, Jie; Yu, Wei-Jia; Sun, Wen-Long (Frontiers in Bioengineering and Biotechnology, 2024)
The clinical application of the recombinant human granulocyte colony-stimulating factor (rhG-CSF) is restricted by its short serum half-life. Herein, site-selective modification of the Nterminus of rhG-CSF with PAL-PEG3-Ph-CHO was used to develop a long-acting rhG-CSF.The optimized conditions for rhG-CSF modification with PAL-PEG3-Ph-CHO were: reaction solvent system of 3% (w/v) Tween 20 and 30 mM NaCNBH3 in acetate buffer (20 mmol/L, pH 5.0), molar ratio of PAL-PEG3-Ph-CHO to rhG-CSF of 6:1, temperature of 20°C, and reaction time of 12 h, consequently, achieving a PAL-PEG3-Ph-rhG-CSF product yield of 70.8%. The reaction mixture was purified via preparative liquid chromatography, yielding the singlemodified product PAL-PEG3-Ph-rhG-CSF with a HPLC purity exceeding 95%. The molecular weight of PAL-PEG3-Ph-rhG-CSF was 19297 Da by MALDI-TOF-MS, which was consistent with the theoretical value. The circular dichroism analysis revealed no significant change in its secondary structure compared to unmodified rhG-CSF. The PAL-PEG3-Ph-rhG-CSF retained 82.0% of the in vitro biological activity of unmodified rhG-CSF. The pharmacokinetic analyses showed that the serum half-life of PAL-PEG3-Ph-rhG-CSF was 7.404 ± 0.777 h in mice, 4.08 times longer than unmodified rhG-CSF. Additionally, a single subcutaneous dose of PAL-PEG3-Ph-rhG-CSF presented comparable in vivo efficacy to multiple doses of rhG-CSF. This study demonstrated an efficacious strategy for developing long-acting rhG-CSF drug candidates.